Cassini observations of ionospheric plasma in Saturn's magnetotail lobes - Felici,M; Arridge,CS; Coates,AJ; Badman,SV; Dougherty,MK; Jackman,CM; Kurth,WS; Melin,H; Mitchell,DG; Reisenfeld,DB; Sergis,N (Journal of Geophysical Research: Space Physics, 2016)
Studies of Saturn's magnetosphere with the Cassini mission have established the importance of Enceladus as the dominant mass source for Saturn's magnetosphere. It is well known that the ionosphere is an important mass source at Earth during periods of intense geomagnetic activity, but lesser attention has been dedicated to study the ionospheric mass source at Saturn. In this paper we describe a case study of data from Saturn's magnetotail, when Cassini was located at 2200 h Saturn local time at 36 RS from Saturn. During several entries into the magnetotail lobe, tailward flowing cold electrons and a cold ion beam were observed directly adjacent to the plasma sheet and extending deeper into the lobe. The electrons and ions appear to be dispersed, dropping to lower energies with time. The composition of both the plasma sheet and lobe ions show very low fluxes (sometimes zero within measurement error) of water group ions. The magnetic field has a swept-forward configuration which is atypical for this region, and the total magnetic field strength is larger than expected at this distance from the planet. Ultraviolet auroral observations show a dawn brightening, and upstream heliospheric models suggest that the magnetosphere is being compressed by a region of high solar wind ram pressure. We interpret this event as the observation of ionospheric outflow in Saturn's magnetotail. We estimate a number flux between (2.95 ± 0.43) × 109 and (1.43 ± 0.21) × 1010 cm−2 s−1, 1 or about 2 orders of magnitude larger than suggested by steady state MHD models, with a mass source between 1.4 ×102 and 1.1 ×103 kg/s. After considering several configurations for the active atmospheric regions, we consider as most probable the main auroral oval, with associated mass source between 49.7 ±13.4 and 239.8 ±64.8 kg/s for an average auroral oval, and 10 ±4 and 49 ±23 kg/s for the specific auroral oval morphology found